Reduction of Solar UV Radiation Due to Urban High-Rise Buildings – A Coupled Modelling Study - Wai, Ka-Ming; Yu, Peter K. N.; Lam, Ka-Se (PLOS ONE, 2015)
Solar UV radiation has both adverse and beneficial effects to human health. Using models (a radiative transfer model coupled to a building shading model), together with satellite and surface measurements, we studied the un-obstructed and obstructed UV environments in a sub-tropical urban environment featured with relatively high pollution (aerosol) loadings and high-rise buildings. Seasonal patterns of the erythemal UV exposure rates were governed by solar zenith angles, seasonal variations of aerosol loadings and cloud effects. The radiative transfer modelling results agreed with measurements of erythemal UV exposure rates and spectral irradiances in UVA and UVB ranges. High-rise buildings and narrow road width (height to width, H/W, ratios up to 15) reduced the modelled total UV (UVA+UVB) radiation and leave 10% of the un-obstructed exposure rate at ground-level at noon. No more than 80% of the un-obstructed exposure rate was received in the open area surrounded by 20-storey buildings. Our modelled reduction of UVB radiation in the urban environment was consistent with similar measurements obtained for Australia. However, our results in more extreme environments (higher H/W ratios) were for the first time reported, with 18% of the un-obstructed exposure rate remained at the ground-level center of the street canyon.